PENGETAHUAN DAN KESADARAN WAJIB PAJAK PADA KEPATUHAN DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN - Raka Nafain, Choirun; Wulandari, Sartika; Meita Oktaviani, Rachmawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
According to applicable legal regulations, taxes are a necessary payment that people or business entities must provide to the state in order to finance its needs and achieve the best possible public welfare. The purpose of this study is to examine how taxpayer awareness and knowledge affect the degree of land and building tax payment compliance in the Semarang City region. The research sample consisted of 120 Semarang City taxpayers in total. Quantitative data, which is derived from respondents' answers to questionnaire questions, is the sort of data used in research. The primary tool for gathering data is the questionnaire, with recordkeeping, literature reviews, and observation serving as auxiliary techniques. The data analysis process involves the use of multiple regression analysis, hypothesis testing, and data quality assessment. The study's findings demonstrate that taxpayers' awareness and knowledge levels have a favorable and significant impact on their compliance with paying land and building taxes.